Altruistic and economic measurements used for prevention health services: Faith community nursing program. (August 2016) - Ziebarth, Deborah
Graphical abstract: Highlights: There is a gap in nursing knowledge about methods to communicate a prevention program's worth. The perception of a prevention program's worth can be continually refined and influenced. Measurements used for "valuing" (estimating worth) of prevention health programming, such as a faith community nursing, are both altruistic and economic. Altruistic measures include story-telling through stories, documentation and activity reports. Economic measures include Net Benefits Analysis of a prevention program, Cost Benefit Analysis of a prevention intervention, Fixed and Variable Cost Percentage considerations. A theoretical model, "Prevention Program Valuing", is presented. This work is important to leverage funding for existing and new disease prevention health programming.